Effects of Different River Crab Eriocheir sinensis Polyculture Practices on Bacterial, Fungal and Protist Communities in Pond Water - Yun Bao; Bing Li; Rui Jia; Linjun Zhou; Yiran Hou; Jian Zhu (Biomolecules)
Microorganisms, including bacteria, fungi, and protists, are key drivers in aquatic ecosystems, maintaining ecological balance and normal material circulation, playing vital roles in ecosystem functions and biogeochemical processes. To evaluate the environmental impact of different river crab polyculture practices, we set up two different river crab (Eriocheir sinensis) polyculture practices: one where river crabs were cultured with mandarin fish (Siniperca chuatsi), silver carp (Hypophthalmichthys molitrix), and freshwater fish stone moroko (Pseudorasbora parva), and another where river crabs were cultured just with mandarin fish and silver carp. These two polyculture practices were referred to as PC and MC, respectively. We analyzed the water bacterial, fungal, and protist communities in the PC and MC groups using 16S, ITS, and 18S ribosomal RNA high-throughput sequencing. We found that the PC group obviously increased the diversity of microbial communities and altered their composition. The bacterial community held the narrowest habitat niche and exhibited the weakest environmental adaption compared to fungal and protist communities. The PC group altered the co-occurrence networks of bacteria, fungi, and protist, leading to more complex and stable communities of fungi and protist. Furthermore, the PC group shifted the assembly mechanism of the bacterial community from being predominantly deterministic to predominantly stochastic processes, with relatively minor impacts on the fungal and protist communities. Environmental factors, especially dissolved oxygen (DO), were significantly associated with the communities of bacteria, fungi, and protists, with DO being the major contributor to changes in the microbial communities. Our results suggest that the polyculture of river crab with mandarin fish, silver carp, and stone moroko was an effective and viable attempt, and it was superior in terms of microbial community diversity and stability.